High IKZF1/3 protein expression is a favorable prognostic factor for survival of relapsed/refractory multiple myeloma patients treated with lenalidomide. Issue 1 (December 2016) - Pourabdollah, Maryam; Bahmanyar, Mohammad; Atenafu, Eshetu; Reece, Donna; Hou, Jian; Chang, Hong
Abstract The aim of this study is to assess nucleoprotein expression of IKZF1/3 in patients with relapsed/refractory multiple myeloma (MM) who received lenalidomide-based therapy and correlated them with their clinical outcomes. A total of 50 patients diagnosed with MM were entered in the study with the median follow-up of 86.4 months. By immunohistochemistry (IHC), IKZF1 and IKZF3 were expressed in 72 and 58% of the cases, respectively. IKZF1 and IKZF3 expressions were associated with longer median progression free survival (P = 0.0029 andP < 0.0001) and overall survival (P = 0.0014 andP < 0.0001). IKZF3 expression also appears predicted a favorable response to the lenalidomide-based therapy.